People-to-People Citizen Ambassador Program: Optometry Delegation - China - Lecker, G (Canadian Journal of Optometry, 2021)
This particular adventure really began on April 25, 1985, when I received an invitation from Dr. Irvin Borish to join an optometric delegation to the People's Republic of China.